International Scientific Conference "The life and works of Jalkhanz Khutagt” (July 24, 2014, Mongolia) - Hertek, Lyubov K.; Kungaa, Margarita B. (The New Research of Tuva, 2014)
International Scientific Conference "The life and works of Jalkhanz Khutagt” (July 24, 2014, Mongolia)